2008
DOI: 10.1007/s11440-008-0075-y
|View full text |Cite
|
Sign up to set email alerts
|

Time dependent deformations during tunnelling and stability of tunnel faces in fine-grained soils under groundwater

Abstract: The measures required for driving a tunnel below the groundwater table depend on the permeability of the soil. In coarse-grained, highly permeable soils additional measures, for example compressed-air support combined with a reduction of the permeability of the soil, e.g. induced by grouting, are necessary. Compared to this, it is possible to do without such measures in fine-grained, cohesive soils because of the increased short-term stability of the tunnel face under undrained conditions. In this publication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…e comprehensive FEM study on the face stability of shield tunnels was carried out by Zhang et al [47,48], who used stepwise-reduced support pressure to achieve collapse failure at the tunnel face and took the critical support pressure to judge whether the face had been damaged. Hö e et al [49,50] studied the stability of the tunnel face through the deformation development law of the surrounding rock at the face and determined whether the face is unstable according to the deformation value of the face. ese studies indirectly described the instability of the face through a certain quantitative index but could not reverse the essential phenomenon that the rock mass at the face fails and breaks away from the matrix due to excessive deformation.…”
Section: Instability Mechanism Of the Facementioning
confidence: 99%
“…e comprehensive FEM study on the face stability of shield tunnels was carried out by Zhang et al [47,48], who used stepwise-reduced support pressure to achieve collapse failure at the tunnel face and took the critical support pressure to judge whether the face had been damaged. Hö e et al [49,50] studied the stability of the tunnel face through the deformation development law of the surrounding rock at the face and determined whether the face is unstable according to the deformation value of the face. ese studies indirectly described the instability of the face through a certain quantitative index but could not reverse the essential phenomenon that the rock mass at the face fails and breaks away from the matrix due to excessive deformation.…”
Section: Instability Mechanism Of the Facementioning
confidence: 99%
“…(13). The term ''simulation cycle'' refers to the swapping process by using the same simulation annealing parameters.…”
Section: Simulated Annealingmentioning
confidence: 99%
“…For example, we may refer to the recent paper [13] investigating the effect of permeability on the deformations of shallow tunnels; also to the paper [12] that investigates the effect of the nature of constitutive model of the soil on the ground deformation behavior around a tunnel. However, past studies [6,7,11,21] have shown that inherent variability of soil or rock masses viewed at the scale of the core or the scale of elements needed for numerical simulations (mesoscale) can produce ground deformation behaviors that are qualitatively different from those predicted by conventional deterministic analyses with averaging of mechanical properties over large volumes such as this of an entire geological unit (macroscale).…”
Section: Introductionmentioning
confidence: 99%
“…Theories and methods of stability analysis of large-section clay tunnels are also based on the stability of ordinary tunnels (Höfle et al, 2008;Lü et al, 2020;Song et al, 2021;Xue et al, 2023b). The tunnel stability problem is derived from the difficulties encountered in the construction of underground projects (Huang et al, 2019;Liu et al, 2020;Kumar and Sahoo, 2021;Zhang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%